Investigation of Swirling Flows in Mixing Chambers - Jyh Jian Chen; Chun Huei Chen (Modelling and Simulation in Engineering)
This investigation analyzed the three-dimensional momentum and mass transfer characteristics arising from multiple inlets and a single outlet in micromixing chamber. The chamber consists of a right square prism, an octagonal prism, or a cylinder. Numerical results which were presented in terms of velocity vector plots and concentration distributions indicated that the swirling flows inside the chamber dominate the mixing index. Particle trajectories were utilized to demonstrate the rotational and extensional local flows which produce steady stirring, and the configuration of colored particles at the outlet section expressed at different Re represented the mixing performance qualitatively. The combination of the Taylor dispersion and the vorticity was first introduced and made the mixing successful. The effects of various geometric parameters and Reynolds numbers on the mixing characteristics were investigated. An optimal design of the cylindrical chamber with 4 inlets can be found. At larger Reynolds number, Re>15, more inertia caused the powerful swirling flows in the chamber, and more damping effect on diffusion was diminished, which then increased the mixing performance.